RELIGION AND ITS IMPACT ON INDIAN SOCIETY - Anupa Singh (International Journal of Multidisciplinary Research and Studies, 2021)
For millennia, religion has played a significant role in the political life, cultural life, and economic life of Indian civilization. Hinduism, Buddhism, Sikhism, and Jainism are all part of India's illustrious religious past, and the country takes great pride in this. In spite of the fact that 79.8% of Indians consider themselves to be Hindus, there are many different religions practiced in India, all of which continue to have an impact on modern culture. The fact that there are so many temples, mosques, and other holy sites in India is evidence that religion plays a more prominent role in Indian society than it does in the majority of English-speaking nations in the West. Scholars live together in huge communities known as ashrams, sometimes known as monasteries or gathering sites. Ashrams often have unique geography, as well as the construction of temples and shrines. Many different sites of worship, such as Hindu temples, Muslim mosques, and Christian churches, can be found in close proximity to one another. We present a quick summary of the major religions that originated in India as well as the major faiths that are practiced in India, despite the fact that it is impossible to cover all religions in India in depth her